Beteende- och konfliktstudie av oskyddade trafikanter vid övergångsställen i närheten av järnvägsstationer – En studie utförd i Lund, Malmö och Helsingborg - Jonasson,Edvard (LUTVDG/(TVTT-5366)/1-136/2025, 2025)
At railway stations many people pass daily commuting to and from work or school, often switching between different forms of transportation. During the change of transportation, the unprotected road users (pedestrians, cyclists, and e-scooters) might need to cross a road at a crosswalk. Depending on the form om regulation of the crosswalk different behaviors and conflicts occurs. Unexpected behaviors among unprotected road users can result in conflict situations. This report aims to contribute with knowledge about conflicts- and behavior of unprotected road users nearby railway stations. Despite the different layouts near the railway stations, it is possible to draw general conclusions about the types of behaviors and conflicts that arise. Video footage captured 12 hours of activity at each station, from 07:00 to 19:00, allowing for a detailed analysis of behaviors and interactions. The study's results showed that pedestrians heading towards the train stations in Lund and Malmö displayed a higher tendency to ignore other traffic and cross against red lights, likely due to higher stress levels among pedestrians. Most conflicts occurred in Lund, which has an unregulated pedestrian crossing. In Helsingborg, the highest number of red-light crossings took place towards the city center. Bus drivers showed a higher tendency not to yield to pedestrians at crossings, regardless of regulation. There were generally very few crossings by cyclists and e-scooters at the pedestrian crossings in both Lund and Helsingborg. The studied crossing in Malmö is located on a cycling path, which results in more bicycle traffic. In Malmö most of the conflicts were between bused and cyclists / e-scooters. E-scooters are often operated at high speeds and with an aggressive riding style. Due to different layouts and conditions, it is difficult to generalize behaviors and conflicts across different train stations. Accidents and conflicts are random, and therefore potential behaviors and conflicts that were not observed may still exist.
Keywords: Oskyddade trafikanter; övergångsställe; järnvägsstation; konflikter; beteende